Discursive elements of verbs of social relation and their categorial features - Nabiyeva Zarrina Isomiddinovna (Zien Journals, 2025)
This article explores the discursive elements of verbs of social relation and their categorial features in modern English. The study analyzes how these verbs function within discourse to express interpersonal interaction, social behavior, and communicative intentions. Special attention is given to their semantic, grammatical, and pragmatic properties, as well as their categorial status within the system of parts of speech. The research identifies that verbs of social relation serve not only as linguistic indicators of social actions but also as important tools for maintaining coherence and interpersonal balance in communication. The findings contribute to a deeper understanding of the relationship between language, discourse, and social interaction.
Keywords: discursive elements; verbs of social relation; categorial features